ELECTRONIC EXAMINATION TASKS CREATION USING DISTANCE LEARNING PLATFORM MOODLE - Lopina, Nataliia (Educological discourse, 2020)
The introduction of distance learning due to the COVID-19 pandemic in the world poses new challenges not only to the organization of the learning process, but also the development of algorithms for distance assessment, development of methods for academic integrity in distance learning platforms in student-teacher interaction. The article provides an algorithm for creating tests in the distance learning system Moodle. The concepts of static and dynamic electronic examination tasks are introduced. Means of control of observance of academic integrity during filling of electronic examination tasks are analyzed: features of test setting (test date, test opening time, test duration, restriction of test availability; availability of the test by group, user profile photo settings for additional identification), means of identification of a distance learning platform (access to electronic examination tasks for registered users in the distance learning platform with login and password identification, personal account, features of the organization of examination in a distance format (combining the answering in the electronic examination task with a synchronous group session (with a moderator and other students) or a personal session (with an examiner)), use of additional plugins of a distance learning platform (for example Safe Exam Browser quiz access rule). Mathematical modeling of combinations probabilities and frequency of meeting of electronic examination tasks of different types during the exam is carried out. Algorithms for creating static and dynamic e-tasks can be used to conduct final exams in a distance learning format, as well as to support a mixed format of education in secondary, specialized, higher education.